Rubidium block and rubidium permeability of the inward rectifier of frog skeletal muscle fibres. - Standen, N B (1980)
1. A three-electrode voltage clamp method was used to investigate the Rb block of inward rectification in frog sartorius muscle fibres. 2. In a solution containing 80 mM-K+, the potassium conductance increased with increasing hyperpolarization to 3.18 +/- 0.11 mS. cm-2 (n = 17) when (V - VK) was -150 mV. In the presence of Rb+, the conductance increased, fell and increased again with increasing hyperpolarization, i.e. the Rb block was first increased and then reduced by increasing hyperpolarization. Increasing [Rb]o increased the block at all voltages. 3. In a solution containing 80 mM-Rb+ (zero K+) inward currents were recorded when the membrane was hyperpolarized beyond about -60 mV. These currents, which were < 10% the amplitude of those in 80 mM-K solution, were blocked by tetraethylammonium ions. 4. Experiments were carried out in solutions either where both [K]o and [K]i were increased, or where [K]o only was increased. The form of the relation between K conductance and membrane potential appeared to depend on [K]o. The magnitude of the conductance appeared to depend on [K]o and on [K]i. 5. So far as the block by Rb+ is concerned, increasing [K]o appeared to enhance the release of Rb block under large hyperpolarizations. Increasing [K]o and [K]i reduced the Rb block at all membrane potentials. 6. The results of experiments in the presence of Rb+ and Cs+ suggest that these two ions do not compete with each other for a site at which they block inward rectification. Rather, over a range of membrane potentials from -25 to -65 mV, the presence of Cs+ enhances the Rb block and vice versa. 7. Single dissected muscle fibres (from semitendinosus) were used to measure sarcoplasmic resistivity in 80 mM-K solution and 160 mM-K (hyperosmotic) solution. The measured values were 163.2 +/- 11.7 omega x cm and 136.1 +/- 16.0 omega x cm, respectively (n = 7). 8. A semi-empirical model is presented, supposing that Rb interacts with a site in the membrane to produce its blocking effect, but is able to move on through into the sarcoplasm. Internal K+ is supposed to reduce the affinity of the site for Rb+; external K+ is able to enhance the moving on of Rb+ into the sarcoplasm. 9. The implications of our experiments for the nature of the permeability mechanism inward rectification are discussed.